[Spanish translation] Benefits of hydrotherapy in patients with chronic obstructive pulmonary disease: additional outcomes of a randomized clinical trial - Gallo-Silva, Bruna (2025)
The objective of this article was to assess the effect of hydrotherapy on the functional status, dyspnea, BODE index, and quality of life in patients with COPD. A randomized, controlled clinical trial was carried out with 24 COPD patients, randomly divided in two groups: 1) aquatic training group (ATG), participating in an aquatic training (AT) program of intermittent (moderate/high) intensity that took place three times a week, for 8 weeks; and 2) control group (CG), which received guidance on a healthy lifestyle and did not participate in supervised exercises. The variables (functional status, dyspnea, BODE index, and quality of life) were assessed before and after the intervention period. The level of significance was established in 5%. Results show that the ATG presented significant improvements in daily life activities (LCADL total Δ score: -10.1, p = .01), in functional status (PFSDQ-M, total Δ score: -16.9, p = .01), dyspnea (ΔMRC: -1.37, p = .003), BODE index (Δ: -1.25, p = .048) and quality of life (total Δ score: -7.4, p = 0.02). The CG did not show any significant changes. As a conclusion, intermittent aquatic aerobic training of moderate/high intensity fostered a clinically relevant improvement for most patients with COPD in terms of quality of life, limitations in daily life activities, dyspnea, and in the BODE mortality predictor index.